Locoregional spread and survival of stage IIA1 versus stage IIA2 cervical cancer - Hongladaromp W. (Asian Pacific Organization for Cancer Prevention, 2014)
This study was undertaken to compare surgical outcomes and survival rates of patients with the 2009 International Federation of Gynecology and Obstetrics (FIGO) stage IIA1 versus IIA2 cervical cancer treated with radical hysterectomy and pelvic lymphadenectomy (RHPL). Patients with stage IIA cervical cancer undergoing primary RHPL between January 2003 and December 2012 at Chiang Mai University Hospital were retrospectively reviewed. The analysis included clinicopathologic variables, i.e. nodal metastasis, parametrial involvement, positive surgical margins, deep stromal invasion (DSI)), lymph-vascular space invasion (LVSI), adjuvant treatment, and 5-year survival. The chi square test, Kaplan-Meier method and log-rank test were used for statistical analysis. During the study period, 133 women with stage IIA cervical cancer, 101 (75.9 %) stage IIA1, and 32 (24.1 %) stage IIA2 underwent RHPL. The clinicopathologic variables of stage IIA1 compared with stage IIA2 were as follows: nodal metastasis (38.6% vs 40.6%, p=0.84), parametrial involvement (10.9% vs 15.6%, p=0.47), positive surgical margins (31.7% vs 31.3%, p=1.0), DSI (39.6% vs 53.1%, p=0.18), LVSI (52.5% vs 71.9%, p=0.05) and adjuvant radiation (72.3% vs 84.4%, p=0.33). With a median follow-up of 60 months, the 5-year disease-free survival (84.6% vs 88.7%, p=0.67) and the 5-year overall survival (83.4% vs 90.0%, P=0.49) did not significantly differ between stage IIA1 and stage IIA2 cervical cancer. In conclusion, patients with stage IIA1 and stage IIA2 cervical cancer have comparable rates of locoregional spread and survival. The need for receiving adjuvant radiation was very high in both substages. The revised 2009 FIGO system did not demonstrate significant survival differences in stage IIA cervical cancer treated with radical hysterectomy. Concurrent chemoradiation should be considered a more suitable treatment for patients with stage IIA cervical cancer.